2018
DOI: 10.3168/jds.2017-14119
|View full text |Cite
|
Sign up to set email alerts
|

An initiator codon mutation in SDE2 causes recessive embryonic lethality in Holstein cattle

Abstract: Researching depletions in homozygous genotypes for specific haplotypes among the large cohorts of animals genotyped for genomic selection is a very efficient strategy to map recessive lethal mutations. In this study, by analyzing real or imputed Illumina BovineSNP50 (Illumina Inc., San Diego, CA) genotypes from more than 250,000 Holstein animals, we identified a new locus called HH6 showing significant negative effects on conception rate and nonreturn rate at 56 d in at-risk versus control mating. We fine-mapp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…Similarly, previous studies showed that haplotypes are not a perfect proxy for causal mutations (Michot et al, 2017;Fritz et al, 2018), and there are instances where 2 different versions of the same haplotype segregate in the population, one with and one without the causal mutation (Kipp et al, 2016;Menzi et al, 2016). Yet, haplotype is a good substitute to avoid carrier-tocarrier mating, when the causal mutation is unknown (VanRaden et al, 2011;Sahana et al, 2013) or when test results are confidential due to patents (Cole et al, 2016).…”
Section: Large-scale Genotyping Confirmed Recessive Inheritance Of Camentioning
confidence: 63%
See 4 more Smart Citations
“…Similarly, previous studies showed that haplotypes are not a perfect proxy for causal mutations (Michot et al, 2017;Fritz et al, 2018), and there are instances where 2 different versions of the same haplotype segregate in the population, one with and one without the causal mutation (Kipp et al, 2016;Menzi et al, 2016). Yet, haplotype is a good substitute to avoid carrier-tocarrier mating, when the causal mutation is unknown (VanRaden et al, 2011;Sahana et al, 2013) or when test results are confidential due to patents (Cole et al, 2016).…”
Section: Large-scale Genotyping Confirmed Recessive Inheritance Of Camentioning
confidence: 63%
“…Previous studies have highlighted the importance of large-scale genotyping to validate candidate causal mutations (Schwarzenbacher et al, 2016a,b;Michot et al, 2017;Fritz et al, 2018). Our team recently excluded a candidate variant in the SHBG gene for MH1 haplotype in Montbéliarde cattle (Fritz et al, 2013) and validated a new causal variant in the PFAS gene (Michot et al, 2017).…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations